Effect of husbandry system on the incidence of lungworm {metastrongylus spp} in pigs in Ibadan, Nigeria (2001)
Detection of helminth infection in pigs by faecal examination was carried out between the months of August and December 1998. Out of430 pigs 64 (14.9%) were positive for Metastrongylus spp. Of these, 10(15.6%) were adults/breeders, 40(62.5%) were weaners/growers, while 14(21.9%) were piglets. Infection rate 8.7% was found in exotic breeds, 15.3% in crossbreed and 100% in local breeds. All intensively managed farms werelungworm-freewhile28.57% and 100% infectionrate respectively, were found on semi-intensively and extensively managed piggeries. The implications of these findings to the pig industry in Nigeria are discussed